2009
DOI: 10.1007/s00240-009-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

Knotted ureteral catheter in an 83-year-old man: case presentation and urological non-invasive management in the elderly

Abstract: Ureteral catheters are important devices in the management of upper urinary tract obstruction; severe complications due to insertion or stent permanence are unusual. We report the clinical case and management of a knotted ureteral stent in an 83-year-old man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Various adjuncts to traction were used, such as shockwave lithotripsy in a patient with an encrusted proximal end 8 and the insertion of lubricant combined with rotation of the stent in a patient with an ileal conduit. 11 In one case where the knot was nonobstructing, traction was applied for successful removal over 3 days. 14 Other methods used included insertion of a stiff Amplatz wire to untie the knot in one case 17 and ureteroscopic manipulation in another.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various adjuncts to traction were used, such as shockwave lithotripsy in a patient with an encrusted proximal end 8 and the insertion of lubricant combined with rotation of the stent in a patient with an ileal conduit. 11 In one case where the knot was nonobstructing, traction was applied for successful removal over 3 days. 14 Other methods used included insertion of a stiff Amplatz wire to untie the knot in one case 17 and ureteroscopic manipulation in another.…”
Section: Discussionmentioning
confidence: 99%
“…9,[10][11][12][13][14][15][16] This, however, can pose the risk of ureteral avulsion. Various adjuncts to traction were used, such as shockwave lithotripsy in a patient with an encrusted proximal end 8 and the insertion of lubricant combined with rotation of the stent in a patient with an ileal conduit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis of previous reports of knotted stent indicated that the male to female ratio is 3:1 and the mean age is 50 years (range, 4-86 years). The knotted stents were located in the upper ureter in 18 cases, the middle ureter in 2 cases, and the distal ureter in 1 case ( Supplementary Table 1 ) [ 4 , 5 , 6 , 7 , 8 ]. The most common reasons for stent placement were ESWL of a renal stone (9 cases), treatment of upper ureter stone or upper ureter obstruction (7 cases), to aid with anastomosis of the ureter (2 cases), periodic stent substitution (2 cases), and interoperative ureter determination (1 case) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another case, the stent was extracted after waiting for status of the percutaneous nephrostomy (PCN). In one case, stent removal was achieved by injecting petroleum jelly in the ureterocutaneostomy [ 5 ]. However, ureteral avulsion is a potential risk of these techniques.…”
Section: Discussionmentioning
confidence: 99%